Contact Mechanics and Friction Physical Principles and Applications - Popov, Valentin L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This application-oriented book introduces readers to the associations and relationships between contact mechanics and friction, providing them with a deeper understanding of tribology. It addresses the related phenomena of contacts, adhesion, capillary forces, friction, lubrication, and wear from a consistent point of view. The author presents (1) methods for rough estimates of tribological quantities, (2) simple and general methods for analytical calculations, and (3) the crossover into numerical simulation methods, the goal being to convey a consistent view of tribological processes at various scales of magnitude (from nanotribology to earthquake research). The book also explores the system dynamic aspects of tribological systems, such as squeal and its suppression, as well as other types of instabilities and spatial patterns. It includes problems and worked-out solutions for the respective chapters, giving readers ample opportunity to apply the theory to practical situations and to deepen their understanding of the material discussed. The second edition has been extended with a more detailed exposition of elastohydrodynamic lubrication, an updated chapter on numerical simulation methods in contact mechanics, a new section on fretting in the chapter on wear, as well as numerous new exercises and examples, which help to make the book an excellent reference guide.  "Popov puts a reader equipped with good intuition into a position to tackle quite a few tribological problems in a semi-quantitative fashion. ... The book is organized extremely well ... The large number of solved problems at the end of each chapter is a definite advantage of the book. ... great benefit to those who teach tribology. ...Meaningful references are provided for those who want to refine the material as a teacher or to indulge in tribological research." (Prof. Martin Müser, Tribology Letters, July, 2010).
Introduction -- Qualitative Treatment of Contact Problems - Normal Contact without Adhesion -- Qualitative Treatment of Adhesive Contacts -- Capillary Forces -- Rigorous Treatment of Contact Problems - Hertzian Contact -- Rigorous Treatment of Contact Problems - Adhesive Contact -- Contact between Rough Surfaces -- Tangential Contact Problems -- Rolling Contact -- Coulomb's Law of Friction -- The Prandtl-Tomlinson Model for Dry Friction -- Frictionally Induced Vibrations -- Thermal Effects in Contacts -- Lubricated Systems -- Viscoelastic Properties of Elastomers -- Rubber Friction and Contact Mechanics of Rubber -- Wear -- Friction Under the Influence of Ultrasonic Vibrations -- Numerical Simulation Methods in Friction Physics -- Earthquakes and Friction -- Appendix -- Further Reading -- Figure Reference -- Index.
Keywords: Mechanics, Applied; Solids; Coatings; Tribology; Corrosion and anti-corrosives.; Mechanical engineering; Condensed matter; Solid Mechanics; Coatings; Tribology; Corrosion; Mechanical Engineering; Condensed Matter Physics